METHODOLOGICAL PRINCIPLES OF OPTIMIZING THE INTERACTION OF TRANSPORT MODES BASED ON ARTIFICIAL INTELLIGENCE - Попова, Яна; Український, Євген (SWorldJournal, 2025)
The article analyzes modern methods of optimizing interaction between different types of transport using artificial intelligence technologies. The research addresses key challenges of transport coordination, such as processing large-scale data, dealing wi